Spanish lessons : film, television, and transmedia in contemporary Spain - Smith, Paul Julian (Berghahn Books, 2017)
Though unjustly neglected by English-language audiences, Spanish film and television not only represent a remarkably influential and vibrant cultural industry; they are also a fertile site of innovation in the production of "transmedia" works that bridge narrative forms. In Spanish Lessons, Paul Julian Smith provides an engaging exploration of visual culture in an era of collapsing genre boundaries, accelerating technological change, and political-economic tumult. Whether generating new insights into the work of key figures like Pedro Almodóvar, comparing media depictions of Spain's economic woes, or giving long-overdue critical attention to quality television series, Smith's book is a consistently lively and accessible cultural investigation.